CHARACTERISTICS OF EUGENOL PRODUCTS AND IN VITRO RELEASE IN GEL BASE WITH HYDROXYPROPYL METHYLCELLULOSE (HPMC) VARIANT AS GELLING AGENT - ROHMANI, SHOLICHAH; YUGATAMA, ADI; WIJAYANTI, ISTI; ERMAWATI, DIAN EKA; ARTANTI, ANIF NUR; KUNDARTO, WISNU; ZULPADLY, M. FIQRI (International Journal of Applied Pharmaceutics, 2021)
Objective: This research was conducted to examine the characteristics of the eugenol gel preparation in the Hydroxypropyl Methylcellulose (HPMC) gel base and to determine the profile of the release of eugenol from the HPMC gel base. Methods: Eugenol was made into gel preparations using HPMC base with concentrations of 3%, 5% and 7%. The evaluation included the tests of product characteristic and eugenol release. The product characteristic test included organoleptic examination (texture, color, and odor) and tests of spreadability, adhesion, and pH. The release test was carried out using cell diffusion and cellophane membranes. Results: All formulas met the pH requirements of topical products that were safe to use. The spreadability test is between 2.97-6.27 cm, adhesion test of products>4 s. The percentage of determination of eugenol content in the gel formula (F1 105.81%), (F2 93.28%) and (F3 98.87%). The cumulative amount of eugenol was F1 (2.563 mg/cm2), F2 (2.224 mg/cm2), and F3 (1.895 mg/cm2). Conclusion: The variation of HPMC as a gel base has effects on the adhesion, spreadability, and the eugenol gel release profile, where the greater the HPMC concentration, the smaller the spreadability, the greater the adhesion, and the lower the eugenol release profile. Based on the data obtained, the Formula 1 had a better release rate.